Teaching Global Warming with Millealab Virtual Reality - Agusty, Alifia Ilwi; Anggaryani, Mita (Universitas Muhammadiyah Makassar, 2021)
Virtual Reality (VR) is a new technology in education applied to the learning process. The development of VR technology in education meets several problems. This research develop a learning media based on virtual reality technology developed by Millealab. Millealab is a platform for developing VR media with more specific features to create a good visualization of reality to support the teaching and learning process. The development of VR media named